Effects of enteral glutamine supplementation on intestinal permeability in acute pancreatitis: A literature review - Evania Astella Setiawan; Diana Sunardi (Indonesian Nutrition Association, 2021)
Background. Glutamine has been shown to improve the gut mucosal barrier. However, the evidence for benefit of enteral glutamine on intestinal permeability in acute pancreatitis (AP) is limited. Objective. To identify the effect of enteral glutamine supplementation on intestinal permeability in patients with AP. Method. A systematic search was conducted by extracting evidence from published studies on enteral glutamine supplementation in three databases (PubMed, Cochrane Central Register of Controlled Trials, and SciElo) relevant to AP from 1 January 2010 till 31 December 2020. Outcomes assessed were intestinal permeability, infectious complication, hospital length of stay, and mortality rate. Results. A total of 6 studies found by search, in which 2 human RCTs with 7 days duration of intervention with 1b-1c quality based on Criteria by Center of Evidence-Based Medicine, University of Oxford. Both studies showed the benefit of early enteral glutamine supplementation on intestinal permeability in patients with AP. Conclusions. Enteral glutamine supplementation has been shown to improve the gut mucosal barrier in AP. Despite its significant improvement in intestinal permeability, glutamine supplementation did not display a consistently positive effect on clinical outcomes.